A mixed methods investigation of emergency communications centre triage in the Government Emergency Medical Services System, Cape Town, South Africa - Alshehri, M.F. (Afr J Emerg Med, 2020)
INTRODUCTION: In order to allocate resources in an effective manner, emergency medical services (EMS) systems use dispatch-based triaging to prioritise patients by acuity. Over-triage, wherein patients are assigned a higher priority level than necessary, can serve as a safety measure. However, it places strain on EMS systems, a problem believed to be experienced by South Africa's Western Cape Government EMS system, with almost half of its calls designated at the highest priority level. To begin improving dispatch within WCG EMS, we aimed to describe the current system by identifying the most common conditions dispatched, and those most perceived to be suffering from over-triage. METHODS: A multi-methods approach was taken: First, a quantitative chart review was used to analyse all calls assigned a dispatch priority by WCG EMS between December 2016 and November 2017. These descriptive data then informed qualitative focus groups to further investigate emergency medical dispatch (EMD). Three focus groups were conducted, each with a convenience sample of staff from: WCG EMS staff, call takers/dispatchers, and call centre managers. Data were reviewed and coded, after which the lead researcher aggregated coded transcripts and conducted thematic content analysis. RESULTS: Seventy-nine condition categories were identified from 649,544 completed patient records for the study period. Non-specific pain accounted for the greatest proportion of dispatched complaints (16.88%), followed by assault with a weapon (10.00%) and respiratory complaints (9.71%). Sixteen WCG EMS personnel took part in focus groups, highlighting challenges of the current EMD system, including time constraints, legal risks, communication, overuse of the system, and lack of training. Chest pain, collapsed/unresponsive patients, and vomiting and diarrhoea were frequently noted to be potentially over-triaged conditions. To improve this, participants suggested trainings, modifications to the electronic EMD system, additional protocols, and public education. CONCLUSION: This study identified where over-triage is possibly occurring in the WCG EMS dispatch system, as well as potential solutions proposed by those working within the system.